Peran Debt Covenants dalam Memitigasi Perilaku Oportunistik Kepemilikan Blockholders dalam Mengatur Rasio Volatilitas Pada Perusahaan yang Menerapkan IAS 41 Agrikultur - Etania Simamora (STIE Indonesia Banking School, 2014)
At first, this study investigates the effect of fair value of IAS 41 Agriculture valuation on volatility ratio. Furthermore, this study was continued by examining the effect of debt covenants on volatility ratio with blockholders ownership as moderating variables, in which the aim of this second study is as the contribution to IAS 41 Agriculture study. The samples of this study are palm oil companies in Indonesia, Malaysia, Singapore and London. By using panel data analysis, this research finds that the fair value of IAS 41 Agriculture measurement and also debt covenants of IAS 41 Agriculture companies does not affect the volatility ratio. Besides that, IAS 41 Agriculture companies who have a good firm level governance also does not affect the volatility ratio. Overall, the findings suggest the palm oil company to implement the IAS 41 Agriculture because that implementation can not cause volatility in companies’ assets and earnings and also the IAS 41 Agriculture companies who have debt covenants does not have affection with the volatility ratio.